Collaborative leadership to subvert marginalisation: The Case of the Socio-educational Team in Los Asperones, Málaga (Spain) - Ruiz-Román, Cristóbal; Herrera-Pastor, David; Juárez-Pérez-Cea, Jesús (Taylor & Francis, 2020)
This article analyses collaborative leadership within a network that consists of socioeducational organisations, both primary and infant schools, and social services, which attempts to subvert the social inequality experienced by those living in Los Asperones, a slum area in Málaga, Spain, who suffer from extreme exclusion. This study is based on evidence from a qualitative ethnographic study which consisted of focus groups and interviews conducted with representatives from all of the groups involved with work in the area, as well as observations of various socio-educational actions. The findings show the foundations, strategies and challenges of collaborative leadership in this setting. The foundations notably included a commitment shared among the agents that are part of the network, the recognition of the value of the ‘other’ and the pre-eminence of ‘we’ over ‘I’, shifting from ‘ego-based leadership’ to ‘eco-based leadership’. The methodological strategies identified were taking co-responsibility for the initiatives undertaken, trust, good communication and negotiating shared time and spaces. The data revealed that the challenges that could weaken or hinder the network's collaborative action were lack of time and political dependencies.
https://openpolicyfinder.jisc.ac.uk/id/publication/6044
Keywords: Marginación social - Málaga; Investigación activa en educación; Collaborative leadership; Network-based work; Marginalisation; Social pedagogy